High-strength low-noise brake friction plate and preparation method thereof

By weaving Xuanwan fibers with other fibers and other fibers into mesh -shaped woven fabrics, combined with porous nanopolymium and other materials, the problem of prostitution fiber reunion is solved, the strength and abrasion resistance of the friction tablet is improved, and the low noise is achieved Brake effect.

CN119350804AInactive Publication Date: 2025-01-24CHANGCHUN TBK SHILI AUTO PARTS CO LTD

Patent Information

Application Number
CN202411907796.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-01-24
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Basalt fibers in existing friction sheet materials are prone to agglomeration, which makes it difficult to abut between the fibers and is difficult to bond with resin or rubber, which in turn affects the strength and noise performance of the friction sheet.

Method used

Blended with adhesive fiber, polytamide fiber and basalt fiber into friction spinning, and woven it with other fibers into mesh -shaped woven fabrics, combined with porous nanoxoxy alumina, six -way boron boronicide and other materials to make mixed materials. And the curing treatment of epoxy resin and chores, forming high -intensity and low noise friction tablets.

Benefits of technology

It effectively improves the mechanical strength and wear resistance of the friction plate material, while reducing brake noise. The test results show that among 2,000 tests, the number of times when the noise is >60dB is only about 10 times.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

A preparation method of a brake friction plate belongs to the technical field of friction plate materials, and adopts viscose, polyimide fiber, polytetrafluoroethylene fiber, carbon fiber and copper fiber to prepare net-shaped woven cloth; the preparation method comprises the following steps: mixing porous nano aluminum oxide, hexagonal boron nitride, zeolite powder, crystalline flake graphite, magnesium oxide, copper powder, potassium hexatitanate whiskers, carbon nanotubes, vermiculite, mica, sodium bicarbonate, 1, 3-bis (tert-butylperoxy isopropyl) benzene, phenolic resin powder, polytetrafluoroethylene powder, epoxy resin and nitrile rubber to prepare a viscous mixture; and adding the mixture into the net-shaped woven cloth, and carrying out heating treatment, compression molding and curing treatment. The wear resistance of the prepared friction material is effectively improved, the friction coefficient reaches 0.469, and the wear rate is 0.13 * 10 <-7 > cm < 3 > (N.M) <-1 >; the impact strength is 2.3 KJ / m < 2 >, and the shear strength reaches 2.8 MPa; the brake noise of the friction plate material is effectively reduced, and the frequency of noise greater than 60dB in 2000 testing processes is only about 10 times.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of friction plate materials, and in particular to a high-strength and low-noise brake friction plate and a preparation method thereof. Background Art

[0002] With the continuous strengthening of environmental awareness and the consumption of fossil fuels, electric vehicles, as a representative of clean energy transportation, have received widespread attention and promotion worldwide. With the rapid development of electric vehicles, electric vehicles are gradually becoming popular. Compared with gasoline / diesel vehicles, electric vehicles do not use engines but electric motors, so the overall power noise of electric vehicles is much smaller, which highlights the noise generated during braking. There are many reasons for the generation of braking noise, among which the performance of the brake pad (friction pad) is one of the important factors affecting braking noise.

[0003] When preparing friction plates, due to the metal components, a large noise will be generated during braking. However, if materials that can reduce noise are added, such as vermiculite, mica, zeolite powder, etc., the performance of the friction plates will be reduced. If the friction plate material formula is improper, the friction performance will be greatly reduced. If the friction plate is too hard, the ingredients are uneven, the friction coefficient is high, the self-excited vibration noise caused by uneven braking, the instantaneous high temperature during braking, and the carbonization and enamelization on the surface will all generate noise.

[0004] Basalt fiber has excellent properties such as high strength and high temperature resistance, so it is often used in the preparation of friction plate materials. However, basalt fiber itself has high rigidity and it is difficult for fibers to bond with each other. It is not easy to bond and bond with resin, rubber, and other fibers. It is easy to clump itself and produce large stress concentration. It is easy to be pulled out and peeled off during use. Summary of the invention

[0005] Based on the above technical problems, the present invention aims to provide a method for preparing a brake friction plate. The method solves the problem that basalt fibers are easy to agglomerate, effectively improves the bonding and cohesion performance of basalt fibers with other fibers, effectively plays a role, improves the strength of the prepared friction plate, and effectively reduces noise.

[0006] Another object of the present invention is to provide a high-strength and low-noise brake friction pad.

[0007] The purpose of the present invention is achieved through the following technical solutions: A method for preparing a brake friction pad, characterized in that it comprises the following steps: (1) viscose fiber, polyimide fiber, and basalt fiber are blended to form friction spinning 1, polytetrafluoroethylene fiber, basalt fiber, and carbon fiber are blended to form friction spinning 2, friction spinning 1, copper fiber, and friction spinning 2 are spun into Z-twisted yarns to prepare plied yarns, and then the plied yarns are made into a mesh woven fabric; (2) preparing a mixed material by taking porous nano-alumina, hexagonal boron nitride, zeolite powder, flake graphite, magnesium oxide, copper powder, potassium hexatitanate whisker, carbon nanotubes, vermiculite, mica, sodium bicarbonate, 1,3-bis(tert-butylperoxyisopropyl)benzene, phenolic resin powder, and polytetrafluoroethylene powder; (3) adding the mixed material into a mixed solvent consisting of acetone and ethanol, mixing evenly, adding epoxy resin and nitrile rubber, heating and stirring to form a viscous mixture; (4) placing a mesh woven cloth in a mold, adding a viscous mixture, and performing a heating treatment after ultrasonic vibration to obtain a matrix; (5) The substrate is compression molded and then cured.

[0008] Furthermore, in the step (1), the plied yarn is prepared by blending viscose fiber, polyimide fiber and basalt fiber in a weight ratio of 1:2:3-4 to prepare friction spun yarn 1, blending polytetrafluoroethylene fiber, basalt fiber and carbon fiber in a weight ratio of 1:1-2:1 to prepare friction spun yarn 2, and Z-twisting the friction spun yarn 1, copper fiber and friction spun yarn 2 in a weight ratio of 2:4:2-3 to prepare the plied yarn with a twist of 120-150 twists, and weaving the plied yarn into a mesh woven cloth with a warp and weft density of 5-8 strands / cm.

[0009] Since basalt fiber itself has high rigidity and difficulty in bonding between fibers, it is not easy to bond and bond with resin, rubber, and other fibers, and it is easy to agglomerate itself, which will produce large stress concentration and be easily pulled out and peeled off during use. In order to solve this problem, in the present invention, part of the basalt fiber is blended with other fibers to form different friction spinning, and finally woven into a mesh woven cloth with copper fiber, basalt fiber, etc., which reduces the gap between fibers, inhibits the agglomeration of basalt fiber, and effectively solves the problem that basalt fiber is difficult to bond and bond with other fibers, thereby alleviating stress concentration.

[0010] The woven structure made of multiple fibers has a certain wavy texture. During the use and friction process, the corrugated texture presents irregular reflection, interrupting the propagation path of noise, effectively blocking the diffusion of noise, reducing its noise frequency and intensity, thereby achieving the effect of reducing noise.

[0011] Furthermore, the mixed material of step (2) comprises, by weight, 5 to 10 parts of porous nano-alumina, 1 to 5 parts of hexagonal boron nitride, 1 to 5 parts of zeolite powder, 5 to 10 parts of flake graphite, 3 to 5 parts of magnesium oxide, 5 to 10 parts of copper powder, 5 to 10 parts of potassium hexatitanate whiskers, 5 to 10 parts of carbon nanotubes, 3 to 5 parts of vermiculite, 5 to 10 parts of mica, 1 to 5 parts of sodium bicarbonate, 0.5 to 2 parts of 1,3-bis(tert-butylperoxyisopropyl)benzene, 10 to 20 parts of phenolic resin powder, and 4 to 8 parts of polytetrafluoroethylene powder.

[0012] Furthermore, in the step (3), the mass ratio of the mixed material, the mixed solvent, the epoxy resin and the nitrile rubber is 2-3:10:1:2, the volume ratio of acetone and ethanol in the mixed solvent is 1:2-4, the heating temperature is 30-35° C., and the stirring is continued for 20-25 hours to form a viscous mixture.

[0013] Furthermore, in step (4), the mass ratio of the mesh woven cloth to the viscous mixture is 1:3-5.

[0014] Furthermore, the heating treatment in step (4) is specifically staged heating, first keeping the temperature at 35-40°C for 2-3 hours, then heating to 55-60°C, keeping the temperature for 4-5 hours, then heating to 70-75°C, keeping the temperature for 4-5 hours, and finally heating to 100-110°C, keeping the temperature for 5-6 hours.

[0015] During the heating process, the fusion and bonding between the filling material and the mesh woven cloth are effectively promoted through a slow gradient heating process. In addition, during the gradient heating process, sodium bicarbonate will continue to decompose, and after releasing gas, a large number of holes will be formed, providing an environment for the subsequent attachment of inorganic materials.

[0016] Furthermore, in step (5), the molding temperature is 140-150°C, the pre-pressing time is 40-50s, the number of pressure relief and exhaust times is 4-8 times, the hot pressing pressure is 9-12MPa, and the pressing time is 10-15min.

[0017] This process promotes the decomposition of 1,3-bis(tert-butylperoxyisopropyl)benzene to produce free radicals, which are freely dispersed on the surface of other inorganic components, enhancing the compatibility between each material and the resin, and is beneficial for the inorganic material to penetrate into the micropores of the epoxy resin, thereby achieving the effect of improving the strength of the material and increasing wear resistance.

[0018] Furthermore, the curing treatment in step (5) comprises four stages, wherein the temperature of the first stage is 80-90°C and the temperature is kept for 1-3 hours, the temperature of the second stage is increased to 110-120°C and the temperature is kept for 3-5 hours, the temperature of the third stage is increased to 150-170°C and the temperature is kept for 2-4 hours, the temperature of the fourth stage is increased to 200-220°C and the temperature is kept for 4-5 hours, and then the temperature is naturally lowered to room temperature and taken out to obtain a high-strength, low-noise brake friction material.

[0019] Since mesh woven cloth is used to wrap the mixture inside for compression molding, during this process, 1,3-bis(tert-butylperoxyisopropyl)benzene will decompose to produce free radicals, which enhances the compatibility between the materials and the resin, and is conducive to the inorganic material entering the micropores of the epoxy resin. The inorganic material is fixed in the epoxy resin through curing, thereby achieving the effect of improving the material strength and increasing the wear resistance. And by wrapping the mixture with mesh woven cloth, the woven cloth plays a skeleton role, so that all materials form a complete whole, and finally improve the overall strength, overcoming the problem of material performance degradation caused by the use of noise-reducing inorganic materials.

[0020] Most specifically, a method for preparing a brake friction pad is characterized by comprising the following steps: (1) viscose fiber, polyimide fiber and basalt fiber are blended in a weight ratio of 1:2:3-4 to prepare friction spinning 1, polytetrafluoroethylene fiber, basalt fiber and carbon fiber are blended in a weight ratio of 1:1-2:1 to prepare friction spinning 2, friction spinning 1, copper fiber and friction spinning 2 are blended in a weight ratio of 2:4:2-3 to prepare a plied yarn by Z twisting the yarn with a twist of 120-150 twists, and the plied yarn is woven into a mesh woven fabric with a warp and weft density of 5-8 strands / cm; (2) Take 5-10 parts of porous nano-alumina, 1-5 parts of hexagonal boron nitride, 1-5 parts of zeolite powder, 5-10 parts of flake graphite, 3-5 parts of magnesium oxide, 5-10 parts of copper powder, 5-10 parts of potassium hexatitanate whiskers, 5-10 parts of carbon nanotubes, 3-5 parts of vermiculite, 5-10 parts of mica, 1-5 parts of sodium bicarbonate, and 0.5-2 parts of 1,3-bis(tert-butylperoxyisopropyl) and stir at 2000-3000 rpm for 5-15 minutes. Then add 10-20 parts of phenolic resin powder and 4-8 parts of polytetrafluoroethylene powder and continue stirring for 20-30 minutes to form a mixed material; (3) add the mixed material to a mixed solvent consisting of acetone and ethanol, stir for 10-15 hours to mix evenly, then add epoxy resin and nitrile rubber, raise the temperature to 30-35°C, and continue stirring for 20-25 hours to form a viscous mixture. The mass ratio of the mixed material, the mixed solvent, the epoxy resin and the nitrile rubber is 2-3:10:1:2, and the volume ratio of acetone and ethanol in the mixed solvent is 1:2-4; (4) placing a mesh woven cloth in a mold, and then adding the viscous mixture prepared in step (4), wherein the mass ratio of the mesh woven cloth to the viscous mixture is 1:3-5, and after ultrasonic vibration, performing a heating treatment, specifically, first keeping the temperature at 35-40°C for 2-3 hours, then heating to 55-60°C, keeping the temperature for 4-5 hours, then heating to 70-75°C, keeping the temperature for 4-5 hours, and finally heating to 100-110°C, keeping the temperature for 5-6 hours, to obtain a matrix; (5) The substrate is compression molded and then cured. The compression molding temperature is 140-150°C, the pre-pressing time is 40-50s, the pressure relief and exhaust times are 4-8 times, the hot pressing pressure is 9-12MPa, and the pressing time is 10-15min. The curing process includes four stages. The temperature of the first stage is 80-90°C and kept warm for 1-3h. The temperature of the second stage is increased to 110-120°C and kept warm for 3-5h. The temperature of the third stage is increased to 150-170°C and kept warm for 2-4h. The temperature of the fourth stage is increased to 200-220°C and kept warm for 4-5h. The material is then naturally cooled to room temperature and taken out to obtain a high-strength, low-noise brake friction material.

[0021] A high-strength and low-noise brake friction pad is characterized in that a mixture is prepared by mixing porous nano-alumina, hexagonal boron nitride, zeolite powder, flake graphite, magnesium oxide, copper powder, potassium hexatitanate whisker, carbon nanotubes, vermiculite, mica, sodium bicarbonate, 1,3-bis(tert-butylperoxyisopropyl)benzene, phenolic resin powder and polytetrafluoroethylene powder, adding the mixture to a mixed solution of acetone and ethanol, adding epoxy resin and nitrile rubber to form a viscous mixture, adding the mixture to a mesh woven cloth made of viscose fiber, polyamide fiber, carbon fiber, polytetrafluoroethylene fiber, copper fiber, basalt fiber and carbon fiber for heat preservation treatment, and curing the mixture after compression molding.

[0022] Furthermore, the mesh woven cloth is made of friction spun yarn 1 made by blending viscose fiber, polyimide fiber and basalt fiber in a weight ratio of 1:2:3~4, friction spun yarn 2 made by blending polytetrafluoroethylene fiber, basalt fiber and carbon fiber in a weight ratio of 1:1~2:1, and friction spun yarn 1, copper fiber and friction spun yarn 2 in a weight ratio of 2:4:2~3 are used to prepare a plied yarn by Z twisting the yarn with a twist of 120~150 twists, and the plied yarn is woven into a mesh woven cloth.

[0023] Furthermore, in parts by weight, the mixture comprises 5 to 10 parts of porous nano-alumina, 1 to 5 parts of hexagonal boron nitride, 1 to 5 parts of zeolite powder, 5 to 10 parts of flake graphite, 3 to 5 parts of magnesium oxide, 5 to 10 parts of copper powder, 5 to 10 parts of potassium hexatitanate whiskers, 5 to 10 parts of carbon nanotubes, 3 to 5 parts of vermiculite, 5 to 10 parts of mica, 1 to 5 parts of sodium bicarbonate, and 0.5 to 2 parts of 1,3-bis(tert-butylperoxyisopropyl), which are stirred and mixed at 2000 to 3000 rpm for 5 to 15 minutes, and then 10-20 parts of phenolic resin powder and 4 to 8 parts of polytetrafluoroethylene powder are added and stirred for 20 to 30 minutes to form a mixture.

[0024] Furthermore, the viscous mixture is prepared by adding the mixture into a mixed solvent consisting of acetone and ethanol, stirring for 10 to 15 hours to mix evenly, adding epoxy resin and nitrile rubber, heating to 30 to 35° C., and continuing to stir for 20 to 25 hours to form a viscous mixture, wherein the mass ratio of the mixture, the mixed solvent, the epoxy resin and the nitrile rubber is 2 to 3:10:1:2, and the volume ratio of acetone and ethanol in the mixed solvent is 1:2 to 4.

[0025] Furthermore, the heat preservation treatment is firstly to keep the temperature at 35-40°C for 2-3h, then to increase the temperature to 55-60°C, keep the temperature for 4-5h, then to increase the temperature to 70-75°C, keep the temperature for 4-5h, and finally to increase the temperature to 100-110°C, keep the temperature for 5-6h to obtain the matrix.

[0026] Furthermore, the curing includes four stages. The temperature of the first stage is 80-90°C and kept warm for 1-3 hours. The temperature of the second stage is increased to 110-120°C and kept warm for 3-5 hours. The temperature of the third stage is increased to 150-170°C and kept warm for 2-4 hours. The temperature of the fourth stage is increased to 200-220°C and kept warm for 4-5 hours, and then naturally cooled to room temperature.

[0027] Furthermore, the molding temperature is 140-150°C, the pre-pressing time is 40-50s, the number of pressure relief and exhaust times is 4-8 times, the hot pressing pressure is 9-12MPa, and the pressing time is 10-15min.

[0028] The present invention has the following technical effects: The friction plate material prepared by the present invention is prepared by spinning basalt fiber and other fibers, and then weaving them into a woven cloth with a certain texture structure, which is wrapped around the outer surface of the material. (1) The wear resistance of the prepared friction material is effectively improved, and the friction coefficient reaches 0.469 and the wear rate is 0.13×10 -7 cm 3 (N·M) -1 ; (2) Improved the mechanical strength of the material, with an impact strength of 2.3KJ / m 2, the shear strength reached 2.8MPa; (3) the brake noise of the friction pad material was effectively reduced. During the 2000 tests, the noise was > 60dB only about 10 times. DETAILED DESCRIPTION

[0029] The present invention is described in detail below through examples. It is necessary to point out that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Those skilled in the art can make some non-essential improvements and adjustments to the present invention based on the above-mentioned contents of the present invention.

[0030] Example 1 A method for preparing a brake friction plate comprises the following steps: (1) viscose fiber, polyimide fiber and basalt fiber are blended in a weight ratio of 1:2:3.5 to prepare friction spun yarn 1, polytetrafluoroethylene fiber, basalt fiber and carbon fiber are blended in a weight ratio of 1:1.5:1 to prepare friction spun yarn 2, friction spun yarn 1, copper fiber and friction spun yarn 2 are blended in a weight ratio of 2:4:2.5 to prepare a plied yarn by Z twisting the yarn with a twist of 120 to 150 twists, and the plied yarn is woven into a mesh woven fabric with a warp and weft density of 5 to 8 strands / cm; (2) Take 8 parts by mass of porous nano-alumina, 4 parts of hexagonal boron nitride, 4 parts of zeolite powder, 6 parts of flake graphite, 4 parts of magnesium oxide, 8 parts of copper powder, 8 parts of potassium hexatitanate whiskers, 8 parts of carbon nanotubes, 4 parts of vermiculite, 8 parts of mica, 4 parts of sodium bicarbonate, and 1 part of 1,3-bis(tert-butylperoxyisopropyl) and stir them at 2500 rpm for 10 min. Then add 15 parts of phenolic resin powder and 6 parts of polytetrafluoroethylene powder and continue stirring for 25 min to prepare a mixed material; (3) Add the mixed material to a mixed solvent consisting of acetone and ethanol, stir for 10 to 15 hours to mix evenly, then add epoxy resin and nitrile rubber, raise the temperature to 35°C, and continue stirring for 24 hours to form a viscous mixture. The mass ratio of the mixed material, the mixed solvent, the epoxy resin and the nitrile rubber is 2.5:10:1:2, and the volume ratio of acetone and ethanol in the mixed solvent is 1:3; (4) placing a mesh woven cloth in a mold, and then adding the viscous mixture prepared in step (4), wherein the mass ratio of the mesh woven cloth to the viscous mixture is 1:4, and after ultrasonic vibration, performing a heating treatment, specifically, first keeping the temperature at 40°C for 2.5 hours, then heating to 60°C for 4.5 hours, then heating to 75°C for 4.5 hours, and finally heating to 105°C for 6 hours to obtain a matrix; (5) The substrate is compression molded and then cured. The compression molding temperature is 145°C, the pre-pressing time is 45s, the pressure relief and exhaust times are 6 times, the hot pressing pressure is 10MPa, and the pressing time is 12min. The curing process includes four stages. The temperature of the first stage is 85°C and kept warm for 2h. The temperature of the second stage is increased to 115°C and kept warm for 4h. The temperature of the third stage is increased to 160°C and kept warm for 3h. The temperature of the fourth stage is increased to 210°C and kept warm for 4h. The material is then naturally cooled to room temperature and taken out to obtain a high-strength, low-noise brake friction material.

[0031] Comparative Example 1 Compared with Example 1, the fiber used in step (1) is directly mixed with the components in step (2) to prepare a mixed material, and the remaining steps are the same as those in Example 1.

[0032] Comparative Example 2 When preparing the mesh woven fabric, no friction spinning is performed by blending. Instead, each fiber is directly used to prepare a twisted yarn, which is then woven into a mesh woven fabric. The remaining steps are the same as those in Example 1.

[0033] According to GB5763-2018, the friction coefficient, wear rate, impact strength, shear strength and other data of the friction plate at different temperatures were tested. According to SAE J2521-2006, the number of occurrences of noise greater than 60 decibels in the range of 2kHz to 17kHz was tested. The total number of tests was 2000 times. The results are shown in Table 1.

[0034] Table 1:

[0035] During the 2000 noise tests, the noise level higher than 60 dB appeared only 11 times in Example 1, while that in Comparative Examples 1 and 2 was more than 100 times, and the friction performance was also significantly lower than that in Example 1. That is, in the present invention, the fiber is first made into friction spinning, then prepared into a plied yarn, and finally woven into a mesh woven cloth, which is used to wrap the remaining raw materials to form an overall structure, which effectively improves the mechanical strength and wear resistance of the material and achieves the effect of noise reduction.

[0036] Example 2 A method for preparing a brake friction plate comprises the following steps: (1) viscose fiber, polyimide fiber and basalt fiber are blended in a weight ratio of 1:2:4 to prepare friction spun yarn 1, polytetrafluoroethylene fiber, basalt fiber and carbon fiber are blended in a weight ratio of 1:1:1 to prepare friction spun yarn 2, friction spun yarn 1, copper fiber and friction spun yarn 2 are blended in a weight ratio of 2:4:2 to prepare a plied yarn by Z twisting the yarn with a twist of 120 to 150 twists, and the plied yarn is woven into a mesh woven fabric; (2) Take 5 parts of porous nano-alumina, 1 part of hexagonal boron nitride, 1 part of zeolite powder, 5 parts of flake graphite, 3 parts of magnesium oxide, 5 parts of copper powder, 5 parts of potassium hexatitanate whiskers, 5 parts of carbon nanotubes, 3 parts of vermiculite, 5 parts of mica, 1 part of sodium bicarbonate, and 0.5 parts of 1,3-bis(tert-butylperoxyisopropyl) and stir them at 2000 rpm for 15 minutes. Then add 10 parts of phenolic resin powder and 4 parts of polytetrafluoroethylene powder and continue stirring for 20 minutes to prepare a mixed material; (3) Add the mixed material to a mixed solvent of acetone and ethanol, stir for 10 hours until evenly mixed, then add epoxy resin and nitrile rubber, raise the temperature to 30°C, and continue stirring for 25 hours to form a viscous mixture. The mass ratio of the mixed material, the mixed solvent, the epoxy resin and the nitrile rubber is 3:10:1:2, and the volume ratio of acetone and ethanol in the mixed solvent is 1:4; (4) placing a mesh woven cloth in a mold, and then adding the viscous mixture prepared in step (4), wherein the mass ratio of the mesh woven cloth to the viscous mixture is 1:3, and after ultrasonic vibration, performing a heating treatment, specifically, first keeping the temperature at 35°C for 3 hours, then heating to 55°C for 5 hours, then heating to 70°C for 5 hours, and finally heating to 100°C for 6 hours to obtain a matrix; (5) The substrate is compression molded and then cured. The compression molding temperature is 140°C, the pre-pressing time is 50s, the pressure relief and exhaust times are 4 times, the hot pressing pressure is 9MPa, and the pressing time is 15min. The curing process includes four stages. The temperature of the first stage is 80°C and kept warm for 3h. The temperature of the second stage is increased to 110°C and kept warm for 5h. The temperature of the third stage is increased to 150°C and kept warm for 4h. The temperature of the fourth stage is increased to 200°C and kept warm for 5h. The material is then naturally cooled to room temperature and taken out to obtain a high-strength, low-noise brake friction material.

[0037] Comparative Example 3 The difference from Example 2 is that di-tert-butyl peroxide is used to replace 1,3-bis(tert-butylperoxyisopropyl) in step (2), and the remaining steps are the same as Example 2.

[0038] Comparative Example 4 Compared with Example 2, the compression molding steps in step (5) are as follows: The molding temperature was 140°C, the pre-pressing time was 50 seconds, the number of pressure relief and exhaust times was 4 times, the hot pressing pressure was 8 MPa, and the pressing time was 15 minutes. The remaining steps were the same as those in Example 2.

[0039] Example 3 A method for preparing a brake friction plate comprises the following steps: (1) viscose fiber, polyimide fiber and basalt fiber are blended in a weight ratio of 1:2:3 to prepare friction spun yarn 1, polytetrafluoroethylene fiber, basalt fiber and carbon fiber are blended in a weight ratio of 1:2:1 to prepare friction spun yarn 2, friction spun yarn 1, copper fiber and friction spun yarn 2 are blended in a weight ratio of 2:4:3 to prepare a plied yarn by Z twisting the yarn with a twist of 120 to 150, and the plied yarn is woven into a mesh woven fabric; (2) Take 10 parts by mass of porous nano-alumina, 5 parts of hexagonal boron nitride, 5 parts of zeolite powder, 10 parts of flake graphite, 5 parts of magnesium oxide, 10 parts of copper powder, 10 parts of potassium hexatitanate whiskers, 10 parts of carbon nanotubes, 5 parts of vermiculite, 10 parts of mica, 5 parts of sodium bicarbonate, and 2 parts of 1,3-bis(tert-butylperoxyisopropyl) and stir at 3000 rpm for 5 min. Then add 20 parts of phenolic resin powder and 8 parts of polytetrafluoroethylene powder and continue stirring for 30 min to prepare a mixed material; (3) Add the mixed material to a mixed solvent of acetone and ethanol, stir for 15 hours until evenly mixed, then add epoxy resin and nitrile rubber, raise the temperature to 35°C, and continue stirring for 20 hours to form a viscous mixture. The mass ratio of the mixed material, the mixed solvent, the epoxy resin and the nitrile rubber is 2:10:1:2, and the volume ratio of acetone and ethanol in the mixed solvent is 1:2; (4) placing a mesh woven cloth in a mold, and then adding the viscous mixture prepared in step (4), wherein the mass ratio of the mesh woven cloth to the viscous mixture is 1:5, and after ultrasonic vibration, performing a heating treatment, specifically, first keeping the temperature at 40°C for 2 hours, then heating to 60°C, keeping the temperature for 4 hours, then heating to 75°C, keeping the temperature for 4 hours, and finally heating to 110°C, keeping the temperature for 5 hours, to obtain a matrix; (5) The substrate is compression molded and then cured. The compression molding temperature is 150°C, the pre-pressing time is 40s, the pressure relief and exhaust times are 8 times, the hot pressing pressure is 12MPa, and the pressing time is 10min. The curing process includes four stages. The first stage temperature is 90°C and kept warm for 1h. The second stage is heated to 120°C and kept warm for 3h. The third stage is heated to 170°C and kept warm for 2h. The fourth stage is heated to 220°C and kept warm for 4h. Then the temperature is naturally cooled to room temperature and taken out to obtain a high-strength, low-noise brake friction material.

[0040] By testing various data indicators of Example 2, Example 3, Comparative Example 3 and Comparative Example 4, the results are shown in Table 2.

[0041] Table 2:

[0042] It can be seen that since 1,3-bis(tert-butylperoxyisopropyl) was not used in Comparative Example 3, the effect of improving the compatibility between various materials and resins during the subsequent compression molding, which is beneficial for inorganic materials to enter the micropores of epoxy resin, is not obvious, resulting in unsatisfactory friction performance and noise reduction performance of the final prepared material. Comparative Example 4 used a lower pressure during compression molding. It was found in numerous experiments that the compression molding effect could be achieved under a pressure of 5-8MPa, but when the pressure was low, the decomposition effect of 1,3-bis(tert-butylperoxyisopropyl) was not good, resulting in unsatisfactory friction performance and noise reduction performance of the final prepared material.

Claims

1. A method for preparing a brake friction plate, characterized in that: The steps include: (1) viscose fiber, polyimide fiber, and basalt fiber are blended to form friction spinning 1, polytetrafluoroethylene fiber, basalt fiber, and carbon fiber are blended to form friction spinning 2, friction spinning 1, copper fiber, and friction spinning 2 are spun into Z-twisted yarns to prepare plied yarns, and then the plied yarns are made into a mesh woven fabric; (2) preparing a mixed material by taking porous nano-alumina, hexagonal boron nitride, zeolite powder, flake graphite, magnesium oxide, copper powder, potassium hexatitanate whisker, carbon nanotubes, vermiculite, mica, sodium bicarbonate, 1,3-bis(tert-butylperoxyisopropyl)benzene, phenolic resin powder, and polytetrafluoroethylene powder; (3) adding the mixed material into a mixed solvent consisting of acetone and ethanol, mixing evenly, adding epoxy resin and nitrile rubber, heating and stirring to form a viscous mixture; (4) placing a mesh woven cloth in a mold, adding a viscous mixture, and performing a heating treatment after ultrasonic vibration to obtain a matrix; (5) The substrate is compression molded and then cured.

2. The method for preparing a brake friction pad according to claim 1, characterized in that: The step (1) of preparing the twisted yarn comprises: blending viscose fiber, polyimide fiber and basalt fiber in a weight ratio of 1:2:3-4 to prepare friction spun yarn 1; blending polytetrafluoroethylene fiber, basalt fiber and carbon fiber in a weight ratio of 1:1-2:1 to prepare friction spun yarn 2; and using friction spun yarn 1, copper fiber and friction spun yarn 2 in a weight ratio of 2:4:2-3 to prepare the twisted yarn by Z twisting the yarn with a twist of 120-150 twists, and weaving the twisted yarn into a mesh woven cloth.

3. A method for preparing a brake friction pad according to claim 1 or 2, characterized in that: The mixed material of step (2) comprises, by weight, 5 to 10 parts of porous nano-alumina, 1 to 5 parts of hexagonal boron nitride, 1 to 5 parts of zeolite powder, 5 to 10 parts of flake graphite, 3 to 5 parts of magnesium oxide, 5 to 10 parts of copper powder, 5 to 10 parts of potassium hexatitanate whiskers, 5 to 10 parts of carbon nanotubes, 3 to 5 parts of vermiculite, 5 to 10 parts of mica, 1 to 5 parts of sodium bicarbonate, 0.5 to 2 parts of 1,3-bis(tert-butylperoxyisopropyl)benzene, 10 to 20 parts of phenolic resin powder, and 4 to 8 parts of polytetrafluoroethylene powder.

4. A method for preparing a brake friction pad according to claim 3, characterized in that: In the step (3), the mass ratio of the mixed material, the mixed solvent, the epoxy resin and the nitrile rubber is 2-3:10:1:2, the volume ratio of acetone and ethanol in the mixed solvent is 1:2-4, the heating temperature is 30-35° C., and the stirring is continued for 20-25 hours to form a viscous mixture.

5. The method for preparing a brake friction pad according to claim 4, characterized in that: In the step (4), the mass ratio of the mesh woven cloth to the viscous mixed material is 1:3-5.

6. A method for preparing a brake friction pad according to claim 5, characterized in that: The heating treatment in step (4) is specifically staged heating, first keeping the temperature at 35-40°C for 2-3 hours, then heating to 55-60°C, keeping the temperature for 4-5 hours, then heating to 70-75°C, keeping the temperature for 4-5 hours, and finally heating to 100-110°C, keeping the temperature for 5-6 hours.

7. A method for preparing a brake friction pad according to claim 6, characterized in that: In the step (5), the molding temperature is 140-150°C, the pre-pressing time is 40-50s, the number of pressure relief and exhaust times is 4-8 times, the hot pressing pressure is 9-12MPa, and the pressing time is 10-15min.

8. The method for preparing a brake friction pad according to claim 7, characterized in that: The curing treatment in step (5) comprises four stages, wherein the temperature of the first stage is 80-90°C and the temperature is kept for 1-3 hours, the temperature of the second stage is increased to 110-120°C and the temperature is kept for 3-5 hours, the temperature of the third stage is increased to 150-170°C and the temperature is kept for 2-4 hours, the temperature of the fourth stage is increased to 200-220°C and the temperature is kept for 4-5 hours, and then the temperature is naturally lowered to room temperature and taken out to obtain a high-strength, low-noise brake friction material.

Citation Information

Patent Citations

  • Automobile friction material and preparation method thereof

    CN106122322A

  • Automotive brake friction material and preparation method thereof

    CN106590531A

  • Low-noise friction material and preparation method thereof

    CN114806500A

Cited By

  • Environment-friendly high-performance copper-free brake pad and processing technology thereof

    CN121517853A